Postpartum Cranial Diabetes Insipidus - Cairns, Ross Andrew (J Endocr Soc, 2021)
Cranial Diabetes Insipidus is a rare diagnosis and rarer still postpartum. We present the case of 24-year-old woman who developed CDI following pregnancy. The patient had developed persistent polydipsia and polyuria 5 months following her first pregnancy. The pregnancy had been complicated by Gestational Diabetes Mellitus, Obstetric Cholestasis and a Postpartum Haemorrhage which had required a 3 unit transfusion of blood. The patient reported feeling fatigued and lightheaded and stated that she had needed to drink water frequently: around 8 litres throughout the day and 4 litres overnight. She reported that she had been unable to breastfeed but the rest of her systemic enquiry was unremarkable. The patient had attributed her symptoms of lethargy to sleepless nights with her new born baby and the polyuria as a consequence of labour and as such had presented for review at her primary care Physician 18 months following delivery. Initial investigations revealed a fasting blood glucose of 4.9 mmol/l, an Adj. Calcium of 2.23 mmol/l and a fasting urine osmolality of 85 mmol/kg. A diagnosis of DI was suspected and was confirmed by water deprivation test: the patient had an inappropriately dilute urine osmolality of 111 mmol/kg when compared to the serum osmolality of 301 mOsm/Kg at the start of the test and her urine failed to concentrate as water was withheld. Administration of DDAVP resulted in appropriate concentration of urine and therefore confirmed the diagnosis specifically as Cranial Diabetes Insipidus. Blood tests revealed normal anterior pituitary function: TSH was 2.78 mU/L, Prolactin was 361 mU/l, LH and FSH were 23.6 U/L and 5.3 U/L, IGF and GH were 197 ug/L and 0.1 ug/l and ACTH was 10 mU/L. Her basal cortisol was 392 nmol/l and was stimulated to 593 nmol/l by SST. MRI Pituitary revealed an unusually flat and broad pituitary gland with a possible tiny lesion in the posterior pituitary suggestive of an adenoma. The patient was established on DDAVP replacement therapy and her quality of life improved: she enjoyed restful sleep and reported less exhaustion. There was no anterior pituitary hormone deficiency 28 months following delivery. DI is a rare diagnosis with an estimated prevalence of 1 in 25000 people. CDI has been commonly reported as being caused by infiltrative or inflammatory pituitary disease, as an iatrogenic sequelae of pituitary surgery or as a result of a congenital defect in the production of vasopressin. We suspect that in this case the patient’s PPH may have resulted in isolated cranial diabetes insipidus though the significance of the MRI scan findings remains unclear. The learning points highlighted by this case are that CDI can occur following pregnancy in an isolated form without anterior pituitary hormone deficiency. We also highlight that patients may misattribute significant symptoms and signs of DI as being a normal part of the postpartum period resulting in a delayed diagnosis.